Yellow‐throated miners Manorina flavigula homogenize bird communities across intact and fragmented landscapes. (14th September 2015) - Kutt, Alex S.; Vanderduys, Eric P.; Perry, Justin J.; Mathieson, Michael T.; Eyre, Teresa J.
Abstract: In Australia, the role of noisy miners M anorina melanocephala in biotic homogenization of the avifauna has been well established in modified landscapes, and is listed as a threatening process under national conservation legislation. However, less is known about the effect of the congeneric and more widely distributed yellow‐throated miner, M . flavigula . In this paper we investigate the relative roles of habitat loss and increased dominance by the yellow‐throated miner in avian homogenization and species functional group decline. We examined bird community data collected from 368 woodland sites across three bioregions. For each site there was a local and a landscape scale measure of remnant vegetation cover. We used both multivariate and regression analysis to test the relative influence of yellow‐throated miner abundance and vegetation on bird community composition. There was clear compositional change and homogenization of the avifauna where yellow‐throated miners were present and vegetation cover was low. The abundance of 40 bird species was predicted by combinations of vegetation cover or yellow‐throated miner abundance, and 31 of these regressions included the term yellow‐throated miner. Of these, there was a negative relationship with 23 species, and 19 of these were insectivores or nectarivores. We postulate that the combination of clearing and yellow‐throated miner abundance can interact to disrupt the ecological function of woodlands, by the depletion of insect‐ and nectar‐feeding species and the disturbance to mixed feeding flocks. We propose future research objectives that include a continental‐scale analysis of the determinants of yellow‐throated miner overabundance, the numerical and geographical thresholds of their potential impacts, and the ecological consequences on both avifauna and the woodlands they inhabit.